ANALISIS RISIKO PENYEBAB KEBAKARAN DI MUSEUM RANGGAWARSITA DENGAN METODE LOSS CAUSATION MODEL - Vita Mardhiyanti Melati; Ekawati Ekawati; Bina Kurniawan; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
The number of fire cases that hit museums, cultural heritage, and other historical buildings that are not known the main cause shows the lack of anticipating losses. Loss Causation Model is a theory of the causes of accidents which contains points and instructions used to understand the cause of an accident. The purpose of this study is to analyze the risk of fire in the Ranggawarsita Museum with the